Foreword - Costa, Rosalina Pisco (2020)
As the shadow follows the body, the English translation of the Chinese idiom chosen as the motto for this Foreword, is metaphorical for this volume of Contemporary Perspectives in Family Research in many ways. Since the beginning of this editorial project, we envisaged the transitions into parenthood as something we knew was colorful, vivid, and dynamic, deeply intertwined in nature and culture, yet scientifically wrapped in many shadows. Some months ago, when we had to choose the title for the volume, the changing nature of parenting appeared to us as the most appropriate formulation to account for such an idea. Today, we can say that we have not deceived ourselves. In gathering and reading the manuscripts received through an international call, we dived into much differentiated, and sometimes contrasting, realities. Despite this, in all of them, we perceived the still-ever-profound changing nature of parenting and the progressive certainty of the importance of using the plural in the title. There is no transition but transitions into parenthood.